Indications of radiation damage in ferredoxin microcrystals using high‐intensity X‐FEL beams. (16th February 2015) - Nass, Karol; Foucar, Lutz; Barends, Thomas R. M.; Hartmann, Elisabeth; Botha, Sabine; Shoeman, Robert L.; Doak, R. Bruce; Alonso‐Mori, Roberto; Aquila, Andrew; Bajt, Saša; Barty, Anton; Bean, Richard; et al.
<x xml:space="preserve">Abstract</x> Proteins that contain metal cofactors are expected to be highly radiation sensitive since the degree of X‐ray absorption correlates with the presence of high‐atomic‐number elements and X‐ray energy. To explore the effects of local damage in serial femtosecond crystallography (SFX), Clostridium ferredoxin was used as a model system. The protein contains two [4Fe–4S] clusters that serve as sensitive probes for radiation‐induced electronic and structural changes. High‐dose room‐temperature SFX datasets were collected at the Linac Coherent Light Source of ferredoxin microcrystals. Difference electron density maps calculated from high‐dose SFX and synchrotron data show peaks at the iron positions of the clusters, indicative of decrease of atomic scattering factors due to ionization. The electron density of the two [4Fe–4S] clusters differs in the FEL data, but not in the synchrotron data. Since the clusters differ in their detailed architecture, this observation is suggestive of an influence of the molecular bonding and geometry on the atomic displacement dynamics following initial photoionization. The experiments are complemented by plasma code calculations.